The impact of a pre-loaded multi-ingredient performance supplement on muscle soreness and performance following downhill running - Ormsbee, M. J.; Ward, E. G.; Bach, C. W.; Arciero, P. J.; McKune, A. J.; Panton, L. B. (Journal of the International Society of Sports Nutrition, 2015)
The effects of multi-ingredient performance supplements (MIPS) on perceived soreness, strength, flexibility and vertical jump performance following eccentric exercise are unknown. The purpose of this study was to determine the impact of MIPS (NO-Shotgun®) pre-loaded 4 weeks prior to a single bout of downhill running (DHR) on muscle soreness and performance. Trained male runners (n = 20) were stratified by VO2max, strength, and lean mass into two groups; MIPS (n = 10) ingested one serving daily of NO-Shotgun® for 28 days and 30 min prior to all post-testing visits, Control (CON; n = 10) consumed an isocaloric maltodextrin placebo in an identical manner as MIPS. Perceived soreness and performance measurements (strength, flexibility, and jump height) were tested on 6 occasions; 28 days prior to DHR, immediately before DHR (PRE), immediately post (POST) DHR, 24, 48, and 72 hr post-DHR. Perceived soreness significantly increased (p < 0.05) post DHR compared to PRE at all time-points, with no difference between groups. Creatine kinase (CK) and lactate dehydrogenase (LDH) increased over time (p < 0.001) with no group x time interactions (p = 0.236 and p = 0.535, respectively). Significant time effects were measured for strength (p = 0.001), flexibility (p = 0.025) and vertical jump (p < 0.001). There were no group x time interactions for any performance measurements. Consumption of MIPS for 4 weeks prior to a single bout of DHR did not affect perceived soreness, muscle damage, strength, flexibility, or jump performance compared to an isocaloric placebo in trained male runners following a single bout of DHR.